Energy Absorption and Failure Mechanism of Aluminium Bi-tubular Cones under Axial Compression - Asad A Khalid; Murhamdilah Murni (International Journal of Integrated Engineering, 2025)
Thin-walled tubes of circular and noncircular cross-sections are increasingly used as energy absorbers in many applications. The most important target of the designers in automotive manufacturing is to develop a structural component that can sustain high loads and absorb high energy to provide more safety to the passengers and the driver of the vehicle. In addition, to protect vehicle components from catastrophic failure during low or high velocity crush condition. Crashworthiness performance of energy absorber component under axial loading depends on the fracture mechanism by which the component collapse. Fracture mechanism of thin-walled metal and composite tubes influenced by the cross-section, design parameters and material used. In the current research, finite element analysis on aluminium bi-tubular cone components under axial loading were conducted. Combined cone-tube consists of 56 mm tube diameter and 65.63 mm cone top diameter with cone semi-apical angles of 5o, 10o, 15o, 20o and 25o were analysed under axial loading. Effect of cone semi-vertex angle (?) for cone-cone, cone-tube and tube-tube arrangements on the load-displacement characteristics and the absorbed energy were investigated. Crashworthiness analysis was conducted on the fractured bi-tubular component. Results presented that the crushing load and energy absorption of the bi-tubular cone-tube and cone-cone enhanced with increasing cone angle from 5o to 15o. Additional increase in the cone angle up to 25o, decreased the energy absorption, and the bi-tubular components sustained lower loads. Initial crush load of the cone-tube bi-tubular component increased from 20.04 kN to 30.50 kN with increasing cone angle from 5o to 15o. The tested bi-tubes fractured by progressive folding accompanied with buckling that resulted in concertina plastic failure mode followed by non-symmetric diamond failure mode.